Potensi β-tricalcium phosphate sebagai kandidat material pulp capping - Eddy; Johanna Halim, Rafhaela; Ratnasari, Dina; Tjandrawinata, Rosalina; Fibryanto, Eko; Livia, Florencia (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
The β-TCP material is a material of ceramic that often used in the medical and dental fields as a bone substitute material because it has biocompatible, bioresorbable and osteoconductive properties. Apart from that, this material is also biocompatible with tooth tissue, is non-inflammatory, and can regenerate dentin. Several studies have shown that the properties of β-TCP material can be a candidate for pulp capping material. These studies have also been carried out on experimental animals and showed good results. This article reviews the potential of β-TCP as a candidate pulp capping material in dentistry.